RP-HPLC Method for the Simultaneous Estimation of Ambroxol Hydrochloride and Fexofenadine Hydrochloride In bulk and in a Tablet Mixture - Prathyusha Buchupalli, Srinivas Medidi (Journal of Applied Pharmaceutical Science, 2015)
A simple, rapid and precise reverse phase liquid chromatographic (RP-HPLC) method was developed and subsequently validated for simultaneous estimation of Ambroxol hydrochloride and Fexofenadine hydrochloride in bulk drug and in a synthetic mixture. The method is based on High Performance Liquid Chromatography (HPLC) on a reversed – phase column, Hypersil ODS C18 (Hypersil ODS 250 x 4.6 mm, 5µ, Make: Thermo Scientific) prepacked column. The separation was carried out using a mobile phase containing a buffer and acetonitrile (56:44 v/v), was pumped at a flow rate of 0.8 mL/min, column temperature at 35º C using UV-detection at 225 nm. Both the drugs were well resolved on the stationary phase and the retention times were around 2.424 minute for Ambroxol hydrochloride and 3.753 minute for Fexofenadine hydrochloride. The method was validated and shown to be linear for both the drugs. The correlation coefficients for Ambroxol hydrochloride and Fexofenadine hydrochloride are 0.9994 and 0.9992 respectively.
Keywords: Ambroxol hydrochloride, Fexofenadine hydrochloride, HPLC, Validation.